Human Resource Management Strategies and Teachers’ Attitude to Work in Public Secondary Schools in North East Senatorial District, Akwa Ibom State - EmediongOkon, Christiana; Daniel , Bridget; Urenma , Michael (Kashere Journal of Education, 2025)
The study examined the Influence of Human Resource Management Strategies on Teachers’ Attitude to Work in Public Secondary School in the Northeast Senatorial District, Akwa Ibom State. Two research questions and two research hypotheses were raised to guide the study. The study adopted an ex-post facto research design and the population of the study consisted of 3,548 teachers from 87 public secondary schools. A sample size of 355 was selected using a multi-stage sampling approach. Structured questionnaires titled “Human Resources Management Strategies Questionnaire (HRMSQ)” and “Teachers Attitude to Work Questionnaire (TAWQ)" were used as instruments for data collection. The instruments were subjected to validation and reliability tests. Cronbach Alpha statistics were used to test the reliability of the instrument and an overall reliability coefficient index of 0.87 and 0.88 were obtained for the two instruments. Data analysis was conducted using linear regression statistics. The results revealed that staff development and staff compensation significantly influenced teachers’ attitude to work in public secondary schools in the North East Senatorial District, Akwa Ibom State. Based on the findings of the study, it was recommended, among others, that Akwa Ibom State Secondary Education Board should further strengthen staff development by organising seminars in order to consolidate the skills of teachers to drive positive attitudes.